DETERMINAN KEJADIAN OBESITAS PADA ANAK SEKOLAH DASAR - Abdul Hairuddin Angkat; Fauzi Romeli; Emi Inayah Sari Siregar; Wanda Lestari (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Along with the rapid development of the times and technology, the nutritional problem in Indonesia is not only a problem of malnutrition but has also entered into a double nutritional problem, namely obesity in school children. There are many factors that influence obesity in school children. The aim of this research is to determine the determinants of obesity in elementary school children. This research uses an analytical observational method with a cross-sectional design. The sample for this research was 43 elementary school students. Obesity was dependent variable meanwhile knowledge, attitudes and junk food intake were independent variables. The sampling technique was purposive sampling. Data analysis with logistic regression test. The results show that knowledge, attitude and junk food intake has a significantly relationship with the incidence of obesity. The dominant determinant was knowledge. The conclusion is that there is a significant relationship between knowledge, attitude, and junk food intake with the incidence of obesity among elementary school children. It is required to analyze another factors related to the incidence of obesity in elementary school children.